Administration of vitamin D3 topical in increasing serum vitamin D level: A literature review - Nafaisa, He Yeon Asva; Waskito, Fajar; Martien, Ronny; Danarti, Retno (UI Scholars Hub, 2024)
Background: Vitamin D is an essential fat-soluble vitamin that is required daily by the body. Deficiency in vitamin D is experienced by most of the world's population. Vitamin D plays a role in maintaining the skin barrier by regulating keratinocyte proliferation and differentiation, promoting filaggrin formation, and intraepidermal lipids. Discussion: The vital role of vitamin D, non-compliance with supplement consumption, and poor nutritional status of adult patients and the elderly with deficiency and insufficiency of vitamin D encourage studies regarding vitamin D delivery via the transdermal route. The lipophilicity of vitamin D allows it to penetrate through the skin barrier. Conclusion: Research indicates that topical application of vitamin D3 is not only safe but also effective in increasing serum vitamin D levels. Thus, topical delivery is a promising alternative method for providing vitamin D supplementation or as a therapeutic option for specific conditions that leads to improved skin hydration and serum vitamin D levels.